THE INFLUENCE OF SOCIAL MEDIA ON ADOLESCENT PSYCHOLOGICAL, COGNITIVE, AND SOCIAL DEVELOPMENT: A CONTEMPORARY ANALYSIS (SYNAPSES: INSIGHTS ACROSS THE DISCIPLINES, 2026)
The rapid growth of digital communication technologies has changed adolescent life. Social media platforms are now central to communication, identity building, and information sharing. While these platforms offer educational and social opportunities, they also bring psychological and cognitive risks. This article examines the varied impact of social media on adolescents, focusing on mental health, identity development, academic performance, and social interaction. By referencing recent research findings and developmental theories, the study highlights the importance of digital literacy and balanced use. The results suggest that the effects of social media are neither strictly positive nor negative. Instead, they depend on how much, why, and in what context it is used.